Just In Time (JIT) Based Manufacturing Innovation for Production Cost Efficiency: Empirical Analysis at CV. Natural - Setiawan, Heri; Susanto, Sani; Rinamurti, Micheline; Chen, Ming; Alfian, Achmad (Ann Publisher, 2025)
Background, The production process at CV Natural is critical because the sales results of the product are to turn the wheels of the company's economy. The duration of production significantly affects the company because of the targets it must meet. In the production process of wooden carpets and various interior mat products from wood, there is much waste of wood raw materials, while if the wood is stored for too long, damage will occur. So, with this waste, there is a waste of storage costs on wood raw materials. Aim: This study aims to determine the application and role of Just In Time (JIT) in the efficiency of the company's production costs. Methods, JIT methods can streamline production costs without having to reduce product quality—determination of the optimal order quantity, applying JIT to the production line with the concept of line balancing. Results: The company's raw material inventory policy is not optimal and has not shown production cost efficiency compared to using the Economic Order Quantity (EOQ) method or the JIT method. Conclusions: if using the EOQ method, the company can save 63.89% or Rp. 113,473,933.41 of production costs, and if using the JIT method, the company can save 95.47% or Rp. 112,332,193.00 of the total inventory cost of Rp. 177,655,932.73. Implication, CV. Natural's JIT implementation has the potential to improve production cost efficiency significantly, provided it is managed with a solid supply chain management strategy and supported by adequate information systems. However, risk mitigation is required through strategic minimum buffers and close supplier relationships.